2013
DOI: 10.1111/j.2047-2927.2013.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischaemic post‐conditioning on the early and late testicular damage after experimental testis ischaemia–reperfusion

Abstract: SUMMARYIschaemic post-conditioning (IPostC) might represent an innovative surgical approach to protect organs from ischaemia and reperfusion (I/R) injury. We investigated the molecular mechanisms underlying the contrasting effects of IPostC on the early and late damage induced by testicular I/R injury. Testis I/R was induced by occluding the right testicular vessels using a clip. Male rats were divided into the following groups: sham, I/R and I/R + IPostC. In the I/R group, the clip was removed after 60 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Similar findings have been observed in previous studies (Minutoli et al, 2014;Parlaktas et al, 2014a,b;Yulug et al, 2014). In our study, the application of TQ was shown to decrease testicular dysfunction and histopathological changes, as reported in previous studies (Gokce et al, 2011;Kanter, 2011b).…”
Section: Discussionsupporting
confidence: 94%
“…Similar findings have been observed in previous studies (Minutoli et al, 2014;Parlaktas et al, 2014a,b;Yulug et al, 2014). In our study, the application of TQ was shown to decrease testicular dysfunction and histopathological changes, as reported in previous studies (Gokce et al, 2011;Kanter, 2011b).…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, Minutoli et al . showed that IPostC protects the testis from the early damage induced by I‐R injury, but it failed to protect against the later damage . Minutoli et al .…”
Section: Iprec and Ipostcmentioning
confidence: 99%
“…Minutoli et al . investigated the role of several molecular mechanisms underlying the effects of IPostC on testicular I‐R injury . IPostC inhibited mitogen‐activated protein kinases, inflammatory cytokines (IL‐6 and TNF‐α) and NF‐κB expression, augmented IκB‐α expression and decreased histological damage in testes subjected to I‐R …”
Section: Iprec and Ipostcmentioning
confidence: 99%
See 2 more Smart Citations